WordNetLoom: a WordNet development system integrating form-based and graph-based perspectives. (1st January 2013) - Piasecki, Maciej; Marcińczuk, Michał; Ramocki, Radosław; Maziarz, Marek
The paper presents WordNetLoom – an application for WordNet development used in the construction of a Polish WordNet called plWordNet. WordNetLoom provides two means of interaction: a form-based, implemented initially, and a graph-based introduced recently. The graphical, active presentation of WordNet structure enables direct work on the structure of synsets and lexico-semantic relations. In the paper, the both means of interaction are compared and the results of the usability evaluation performed on a group of experienced WordNetLoom users are presented. Directions of the application development were identified. A new version of WordNetWeaver – a tool supporting semi-automated WordNet expansion – is also presented. The new version is based on the user interface similar to WordNetLoom, utilises all types of WordNet relations and is embedded in WordNetLoom. The paper discusses also the role of the application in WordNet development and the extent to which the application can be used for other WordNets. A set of WWW-based tools supporting team work coordination and verification is presented, too.